Agroforestry governance for operationalising the landscape approach: connecting conservation and farming actors - Zinngrebe, Yves; Borasino, Elena; Chiputwa, Brian; Dobie, Philip; García, Edwin; Gassner, Anja; Kihumuro, Heru; Liswanti, Nining; Makui, Permutia; Plieninger, Tobías; y dos autores más (Springer, Berlín (Alemania), 2020)
Special feature: original article